α-amylase inactivation during wheat starch hydrolysis process - Özbek, B; Yüceer, S (ELSEVIER SCI LTD, 2001)
The work reported here investigates the effects of operating conditions on enzymic hydrolysis of wheat starch. A commercial alpha -amylase enzyme (Gemsize 4A, produced by Bacillus subtilis) was used for the hydrolysis experiments. The degree of hydrolysis (%) and alpha -amylase activity (%) were investigated versus the process variables, pH, temperature, viscosity, amount of enzyme preparation added, impeller speed, amount of hydrolysate added and processing time. Optimal conditions have been determined as temperature 60 degreesC, impeller rate 300 rpm and pH 6.5. At these process conditions, alpha -amylase enzyme lost 48% activity and the degree of wheat starch hydrolysis was 40%. Mathematical models depending on the operating conditions were derived using experimental data on residual starch concentration. Some inactivation models were tested for understanding the relationship between the process variables and enzyme stability during the hydrolysis process. (C) 2001 Elsevier Science Ltd. All rights reserved.
Keywords: wheat starch hydrolysis; alpha-amylase enzyme inactivation; process variables; mathematical modelling; stirred batch bioreactor; KINETICS; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology; Engineering